The Theoretical-methodological Basis of the Research Investigation Reflection Preparedness Students of Social Science on the Teaching Practice - Vašátová, Pavlína (Civilia, 2013)
The aim of the article is to describe the theoretical and methodological basis of the research plan, when analysis of pedagogical communication between the student to practice (a teacher) and a pupil is deemed reflective element of possible innovative changes in the professional study programme didactics social of sciences with an emphasis on education. This program is guaranteed by the social sciences of the Faculty of education at Palacky University in Olomouc in the Czech Republic. Conclusions based on the data they can open a possible discussion after changes in the content filling (for example strengthening the teaching of each area) industry didactics in training future teachers study program social sciences with an emphasis on education.
Keywords: Student; Teacher; Planning; Structure; Pedagogy; Teaching; Communication; Reflection questions; Forms; Methods; Subject matter didactics